Trends of Fatal Poisoning in Jhalawar Region of Rajasthan: A 5 - Year Retrospective Study - Ramakant Verma; Khushpal Singh Rathore; Bhavesh Bohra (Institute of Medico-legal Publications Pvt Ltd, 2021)
India is predominantly an agriculture based economy. Problem of poisoning is one of the importantcauses of mortality and morbidity in India and other agriculture based developing countries due to easyavailability, low cost and no restriction on sale and supply of insecticidal compounds. The aim of this studyis to find out the association of episodes of fatal poisoning with various factors like age, gender, area ofresidence, religion, occupation type of poison and manner of death. This retrospective study was carriedout on total poisoning cases brought to mortuary of Jhalawar Medical College and associated group ofhospitals, Jhalawar (Rajasthan) in 5 year duration from 1st January 2014 to 31st December 2018. In thisstudy maximum cases of poisoning were of age group 21 - 30 year, incidence were more among malesbelonged to rural population who were involved in agricultural work. Majority of poisoning cases were dueto Organophosphorus compounds.